Double and Triple Photoionization of CCl4 - Antônio Carlos Fontes dos Santos; Joselito Barbosa Maciel; Alexandre Braga Rocha; Gerardo Gerson Bezerra de Souza (Atoms)
(1) Background: Fragmentation after double and triple photoionization of the CCl4 molecule in the valence, Cl 2p, and C 1s regions have been reported; (2) Methods: We have used photoion-photoion (PIPICO) coincidence technique combined with synchrotron radiation. In addition, ab initio quantum mechanical calculations were done at multiconfigurational self-consistent and multireference configuration interaction to describe ground and inner-shell states; (3) Results: We have observed coincidences involving singly and doubly charged fragments coming from the doubly and triply ionized molecule. We have also found a well agreement between the quantum mechanical calculations and the total ion yield spectrum. It is shown that the Cl+ ion is the predominant product resulting from the fragmentation of the doubly and triply charged CCl4 molecule. The CCl+ + Cl+ pair is the dominant coincidence in the spectra from valence up to the C 1s edge; (4) Conclusions: The kinetic energy of the fragments is compatible with the Coulomb explosion model.